(untitled) (Journal of the Entomological Research Society, 2019)
The purpose of this paper is to identify the nest materials, some physical characteristics and the elemental composition of the nest of Sceliphron curvatum (Smith, 1870). The nest surfaces were observed with a stereomicroscope and scanning electron microscope (SEM). In the inner surface of the S. curvatum nest of the fibers in the mud-ball nest varied between 427 nm and 6300 nm, respectively and averaged 1465.730 nm. The thickness of the fibers in the outer and the inner surface section of the mud nest were between 14 nm and 1430 nm, respectively and averaged 629.373 nm. The nitrogen concentration was 3.94%, the percentages of the saliva, soil and the water absorption capacity were calculated to be 4.848%, 95.152%, and 18.51%, respectively. However, the amount of the elements carbon (C), hydrogen (H), sulphur (S) and nitrogen (N) in the nest was found to have a value of 3.38, 1.526, 0.020 and 0.38 weight % respectively. The colors of the individual mud pots are composed of building materials of different origin and with different shades of almost white over light brown to greyish black with long dark and light brown lines. We have found that the ratios and amount of physical characteristics, elemental composition and the fibers in the mud-ball of the nest of S. curvatum change with soil structure in which nest is built.